2010
DOI: 10.1111/j.1750-3841.2009.01433.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate Type Affects the Quality of Injected Catfish Fillets

Abstract: Use of an agglomerated phosphate blend with a high pH (AGSP) maximized the yield of catfish fillets that were marinated through multineedle injection. In addition, STP and agglomerated phosphate blends increased the yield and tenderness of catfish fillets when compared to the nonmarinated control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 20 publications
5
27
0
Order By: Relevance
“…This suggests that fillet firmness was more uniform and consistent in injected fillets than in noninjected fillets. These results are supported by those observed by Kin et al [26]. [36].…”
Section: Texturesupporting
confidence: 90%
See 4 more Smart Citations
“…This suggests that fillet firmness was more uniform and consistent in injected fillets than in noninjected fillets. These results are supported by those observed by Kin et al [26]. [36].…”
Section: Texturesupporting
confidence: 90%
“…The decrease in lightness as a result of brine injection in muscle products is well documented [16,21,26,35]. Previous study reported that CIE * values of catfish fillets that were injected with agglomerated phosphates were lower than noninjected fillets [26]. Decreased * values were attributed to phosphates from the brine enhancing water holding and therefore resulting in less liquid on the surface to cause light scattering.…”
Section: Colormentioning
confidence: 92%
See 3 more Smart Citations